Synthesis of Corrosion Inhibitors Based on ((1,2- Diphenylhydrazinyl)(3-Nitrophenyl))Methyl Phosphine Acid and its Properties (Texas Journal of Medical Science, 2023)
this paper presents the synthesis and identification of ((1,2-diphenylhydrazinyl)(3- nitrophenyl))methyl phosphinic acid (DFGNFMFK) and the corrosion rate and protection levels of DIIMFK inhibitor in Fon-1 Fon-2 and Fon-3 working solutions at different temperatures and concentrations .